Concession bargaining: An experimental comparison of protocols and time horizons - Federica Alberti; Sven Fischer; Werner Güth; Kei Tsutsui (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
Concessions try to avoid conflict in bargaining and can finally lead to an agreement. Although they usually are seen as unfolding in time, concessions can also be studied in normal form or by conditioning only on failure of earlier agreement attempts. We experimentally compare three protocols of concession bargaining, the normal form or static one, the one where concessions only condition on earlier failures and the truly dynamic one. In spite of their considerable differences in conditioning, the three protocols do not differ in agreement ratio, efficiency and inequality of agreements. There are, however, effects of the maximal number of trials to reach an agreement by concession making and of protocol on when to abstain from conceding.
Keywords: C72; C78; 330; concession bargaining; conflict; deadline; dynamic interaction; emotions; experiment